Application of the Suitability Validation Results During Selection - Balla, József; Szatmári, Adrienn; Kui, László (Magyar Rendészet, 2019)
Regarding law enforcement agencies, the selection of the appropriate staff members and the people who are qualified for professional service has received a lot of attention in the past decade, both at departmental and executive level. Along with this, aptitude tests, selection procedures, and subsequent fitting tests provide many data for the effective organisational operation and its prediction. This study looks at relevant processes within law enforcement organisations, focusing on the border police officers’ suitability criteria.